Afterword: For a Synaesthetics of Seeing. Issue 1 (1st March 2021) - Dave, Naisargi N.
Abstract: This Afterword explores the volume's ambivalent relationship to witnessing, and argues for a synaesthetics of seeing. Drawing on literature fictive and otherwise, with an emphasis on animality (fictive and otherwise), it reflects on how sound and touch enable us to see.